O letramento literário na EJA: uma proposta didática permeada por crônicas e RPG - Oliveira, Taíza Ferreira de (2020)
This work approaches the literary literacy carried out through the reading of literary texts and the development of an RPG game, from which a critical and characteristic reading by students - young people and adults in the education network - develops from their interpretations. The project aims to develop activities based on the basic reading sequence proposed by Rildo Cosson (2009), so that students develop reading and writing skills, being interested in literary reading in an alternative approach to the text as a mere pretext for studying structures language, reading verification sheets and tests. To support the work, a newsletter on the EJA was drawn up, with the authors Freire (1967) and Arroyo (2017), the chronic genre was approached with Bakhtin (1997) and Cândido (1987), the critical reading and classification anchored in the authors Petit (2008) and Rouxel (2012) and also games and learning from the ideas of Huizinga (2005) and Vigotski (2008). It was intended through reading and playful in the Portuguese language classroom, in literature classes, to reach literary literacy. Bearing in mind that the PCNs and a BNCC cover the teaching of the Portuguese language through textual genres, the work presents a didactic proposal for the development of literary literacy through the reading of texts of the chronic genre. In order to achieve the proposed objectives, the research methodology was anchored, based on the methodological assumptions of Thiollent (1996), as well as qualitative research. It was hoped with this work to train readers, with reading skills beyond the walls of the school, and to contribute with other teachers who can use this didactic proposal in their classroom practices.